(untitled) (Journal of Applied Oral Science, 2022)
Objective: To determine the effectiveness of chlorhexidine 0.12% mouthwash (CHX) after tooth extraction for the prevention of alveolar osteitis (AO). Material and methods: We conducted a double-blind randomised clinical trial stratified by risk factors. We enrolled a cohort of 822 patients who underwent dental extractions, and were considered to be at risk of developing AO (previous surgical site infection, traumatic extraction, and tobacco smoking). After extraction, patients were randomly allocated for CHX group or placebo group, matched by risk factors. The primary outcome was clinical diagnosis of AO: increasing postoperative pain for 4 d within and around the socket, and total or partial breakdown of the blood clot in the socket with or without bone exposure. Results: Follow-up was completed by 744 participants (372 chlorhexidine and 372 placebo). We detected no significant differences between the two groups at baseline. After completed follow-up, risk factors were equally distributed between the two groups. Overall incidence of OA was 4.97%, in which 27 participants treated with placebo (7.26%) and 10 participants treated with CHX (2.69%) developed AO. CHX reduced the incidence of AO by 63% [Absolute Risk Reduction: 4.57 (95% CI 1.5-7.7), Number Needed to Treat: 21.88 (95% CI 13.0-69.3), Fisher's exact test: p=0.006]. No adverse effects were reported. Conclusion: The use of chlorhexidine 0.12% mouthwash after tooth extraction is safe and effective in reducing the incidence of AO in high-risk patients.